2022
DOI: 10.1186/s12877-021-02702-z
|View full text |Cite
|
Sign up to set email alerts
|

Patients’ and healthcare providers’ perceptions and experiences of telehealth use and online health information use in chronic disease management for older patients with chronic obstructive pulmonary disease: a qualitative study

Abstract: Background Telehealth and online health information provide patients with increased access to healthcare services and health information in chronic disease management of older patients with chronic diseases, addressing the challenge of inadequate health resources and promoting active and informed participation of older patients in chronic disease management. There are few qualitative studies on the application of telehealth and online health information to chronic disease management in older pa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(33 citation statements)
references
References 78 publications
(69 reference statements)
1
23
0
Order By: Relevance
“…However, as the authors reported that they found no talk about online health information in the observational data, the results are focused upon the interview data. Ten studies addressed patient perspectives on the topic of online information in the communication between health personnel and patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] in different medical areas: Patients with chronic disease [ 17 , 18 , 19 ], or gynecologic or breast cancer [ 15 ]; senior citizens [ 16 , 23 ]; parents or mothers to be [ 21 , 24 ]. Additionally, four articles addressed the practitioners’ perspective [ 21 , 23 , 25 , 26 , 27 ] and two articles described interviews from both patients and practitioners’ perspective [ 13 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…However, as the authors reported that they found no talk about online health information in the observational data, the results are focused upon the interview data. Ten studies addressed patient perspectives on the topic of online information in the communication between health personnel and patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] in different medical areas: Patients with chronic disease [ 17 , 18 , 19 ], or gynecologic or breast cancer [ 15 ]; senior citizens [ 16 , 23 ]; parents or mothers to be [ 21 , 24 ]. Additionally, four articles addressed the practitioners’ perspective [ 21 , 23 , 25 , 26 , 27 ] and two articles described interviews from both patients and practitioners’ perspective [ 13 , 17 ].…”
Section: Resultsmentioning
confidence: 99%
“…Ten studies addressed patient perspectives on the topic of online information in the communication between health personnel and patients [ 13 , 14 , 15 , 16 , 17 , 18 , 19 , 20 , 21 , 22 , 23 , 24 ] in different medical areas: Patients with chronic disease [ 17 , 18 , 19 ], or gynecologic or breast cancer [ 15 ]; senior citizens [ 16 , 23 ]; parents or mothers to be [ 21 , 24 ]. Additionally, four articles addressed the practitioners’ perspective [ 21 , 23 , 25 , 26 , 27 ] and two articles described interviews from both patients and practitioners’ perspective [ 13 , 17 ]. In the results section, we will present a descriptive overview of the main findings from the patients’ perspectives and the health care practitioners’ perspectives, respectively, on the topic of online health information.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…This new form of communication provides broader and open access to information and advices on how to maintain or improve health and manage illness. The use of the Internet and health information may be particularly beneficial to older adults seeking health information [ 17 , 18 ]. However, little is known about the proportion of older adults with physical multi-morbidity who use the Internet to search for health information and communicate with health care providers online [ 11 , 19 ].…”
Section: Introductionmentioning
confidence: 99%